Pembangkitan Fraktal Koch Anti-Snowflake (m,n,c) Menggunakan Metode Transformasi Affine - Alkhori, Ellenda Alkhori; Purnomo, Kosala Dwidja; Juliyanto, Bagus (Mathematics Department, 2019)
Fractal Koch Anti-Snowflake (m,n,c) is a developmental form of fractal Koch Anti-Snowflake (m,n,c) with variation of m is initiator (basic form) using polygon-m and with variation of n is generator (iteration) using polygon-n. While c the size of the middle segment that removed on each side of initiator. Each iteration on generation procedure of Koch Anti-Snowflake (m,n,c) using affine transformation method will produce several forms, the first form is Koch Anti-Snowflake (m.n,c) that does not intersect with variation of initiator polygon-m, variation of generator polygon-n, and the selected c value that is a half the upper limit value ​​have been specified. The Second forms is Koch Anti-Snowflake (m,n,c) coincide with a variation of the initiator polygon-m, variation of generator polygon-n and there are variation value of c which is less than half of the upper limit in the value of c selected. The third form is Koch Anti-Snowflake (m,n,c) intersect with a variation of the initiator polygon-m and variation of generator polygon-n, variation of the initiator polygon-m and variation of generator polygon-n with the selected variation c value which is close enough with the upper limit of value specified is c-0,00001.